1995
DOI: 10.1002/ijc.2910620210
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a low‐fat diet reduces the occurrence of non‐melanoma skin cancer

Abstract: The effect of a low-fat diet on occurrence of non-melanoma skin cancer was examined in a 2-year dietary intervention trial. A total of 101 skin-cancer patients were randomized either to a control group that consumed, on average, 38% of caloric intake as fat, and in which no changes in dietary habits were introduced, or to a low-fat dietary-intervention group, in which patients were instructed to limit their calories from fat to 20% of total caloric intake. Patients were examined at 4-month intervals by dermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 11 publications
1
64
1
1
Order By: Relevance
“…As mentioned earlier, BCC risk may be decreased with a low-fat diet (Black et al, 1995). It is unclear what component of a low-fat diet may be responsible for the anti-BCC effect.…”
Section: A New Interpretation Of the Role Of Sunlight And Diet In Bccmentioning
confidence: 91%
See 2 more Smart Citations
“…As mentioned earlier, BCC risk may be decreased with a low-fat diet (Black et al, 1995). It is unclear what component of a low-fat diet may be responsible for the anti-BCC effect.…”
Section: A New Interpretation Of the Role Of Sunlight And Diet In Bccmentioning
confidence: 91%
“…One provocative study has suggested that BCC may also be prevented with a low-fat diet. In a randomized clinical trial, one hundred patients who had already developed one non-melanoma skin cancer were placed on either a normal or a low-fat diet, and followed for 2 years for the development of skin cancer (Black et al, 1995). A low-fat diet was found to reduce significantly the occurrence of BCCs in this randomized, cohort study (Black et al, 1994;Black et al, 1995).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…These food groups or their major nutrient content have previously been demonstrated in in vitro, animal or human studies to prevent photocarcinogenesis or have shown to be associated with non-melanoma skin cancer. This includes foods rich in antioxidants (fruits, vegetables; Kune et al, 1992;Heinen et al, 2007); high or low in fat (low-fat dairy, processed meat, red meat, poultry; Black et al, 1995;van Dam et al, 2000); high in omega-3 (n-3) fatty acids (oily fish; Black and Rhodes, 2006) or high in other polyphenolic compounds (Hakim et al, 2000). The daily intakes of food groups (in grams) were calculated by summing intakes of individual foods comprising each food group for each participant.…”
Section: Assessment Of Dietary Intakementioning
confidence: 99%
“…Reactive oxygen species (ROS), causing damage to DNA, proteins and lipids, have been associated with carcinogenesis, coronary heart disease and many other health problems (Black et al 1995;Cadenas and Davies 2000). Minimizing oxidative damage may well be one of the most important approaches to prevention of these oxidative stress-related diseases and health problems, since antioxidants terminate direct ROS attacks and radicalmediated oxidative reactions (Burits and Bucar 2000;Yu et al 2002).…”
Section: Introductionmentioning
confidence: 99%